Infection Level of Pathogenic Bacteria in Pork at Traditional Market in Denpasar - Puspawati, Ni Nyoman (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 2 No 1 (2015), 2015)
The aim of the research were to achieve scientific information about the infection level of bacteria found in pork meat and to acquire the information of the sanitation level of the meat stall in traditional market around Denpasar. This research used survey method in sampling before being analyzed in Laboratorium. There are 16 traditional market in Denpasar, based on the minimum survey of sampling which is 30%, 4 market has chosen for sample source . The parameter of this research is total of Coliform , total of E.coli and Salmonella sp , also the sanitation level and hygiene of the butcher using questionare. The result of the research showed that the infection level of Coliform in pork found in the market has been over the limit of SNI which is on the morning market of Badung is (2.5 ± 1.7) x 10 5 cfu/cm 2 , Impres Sanglah market is (7.3 ± 1.2) x 10 4 cfu/cm 2 , Ubung market is (2.9 ± 4.1) x 10 4 cfu/cm 2 and Kreneng market is (1.4 ± 1.5) x 10 4 cfu/cm 2 . The infection level of E. coli found in pork is over the limit of SNI, which is on the morning market of Badung is (5.7 ± 8.2) x 10 4 cfu/cm 2 , Impres Sanglah market is (2.3 ± 2.8) x 10 4 cfu/cm 2 ,  Ubung market is (1.4 ± 1.6) x 10 4 cfu/cm 2 and Kreneng market is (8,3 ± 1,1) x 10 3 cfu/cm 2 . The infection level of Salmonella sp found in pork is over the limit of SNI, which is Impres Sanglah market (6.6 ± 1.1) x 10 3 cfu/cm 2 ,on the morning market of Badung is (5.6 ± 7.5) x 10 3 cfu/cm2, Ubung market is (5.2 ± 6.8) x 10 3 cfu/cm 2 and Kreneng market is (3.2 ± 3.9) x 10 2 cfu/cm 2 . The source of contamination come from the surroundings of the butcher stall in the market that is lack of hygiene and sanitation standard
Keywords: bacteria infection, pork, traditional market